Iranian Elderly Experiences With Myocardial Infarction - Masoud Falahi Khoshknab; Parkhideh Hasani; Ardeshir Afrasiabifar; Farideh Yaghmaei (University of Social Welfare & Rehabilitation Sciences, 2008)
Objectives: Awareness of elderly patients' experiences of myocardial infarction can assist to identify their need, problems, as well as promote their quality of lives. However, there is a little information about how elderly people experience myocardial infarction. This study aimed to explore elderly patients experience with myocardial infarction and their coping strategies. Methods & Materials: This paper is a part of a larger grounded theory. Eight old age patients (65+ years) with first time myocardial were interviewed as purposeful and theoretical sampling. Semi-structure interviews were used for data collection. Data collection and analysis were simultaneously conducted using Strauss and Corbin's grounded theory approach. The trustworthiness of data is confirmed through Lincoln and Guba' s criteria. Results: Elderly patient's experiences of myocardial infarction were categorized as two main themes include: living in the shadow of fear, live with limitation, and their coping strategies namely as return to active life. Living in the shadow of fear is consisted of sub themes named fear of death/reinforcing, fear of physical inability, and fear of dependency on others. Live with limitation composed of feeling of physical incapacity, bodily symptoms, and adherence of medical regimen/family. Return to active life includes positive thinking and self-reliance. Conclusions: Elderly people with first time myocardial infarction experience severe stresses and more limitations due to suddenly threatening their lives and health. Adopting positive coping strategies could facilitate return to normal life and promote their quality of life.